Meta Analysis the Effect of Body Mass Index on the Flat Foot Incidence - Philipus Prihantiko Kurniagung; Dono Indarto; Setyo Sri Rahardjo (Masters Program in Public Health, 2020)
Background: Musculoskeletal disorders in the form of flat foot, back pain and knee pain are often found in people who are obese. Flat foot is a musculoletal disorder characterized by a decrease or decrease in the height of the medial arch as a parameter, especially those that can be observed and measured in height. This study aims to estimate the average size of the effect of BMI on the risk of flat foot.Subjects and Method: Meta-analysis study and systematic reviews were applied to this study using the electronic database Pubmed, Science Direct, Google Scholar and Springer Link. Keywords to search for articles are as follows: